Health care financing and income inequality in Nigeria. Issue 11 (7th October 2020) - Oburota, Chukwuedo Susan; Olaniyan, Olanrewaju
Abstract : Purpose: The purpose of this paper is to decompose the inequities induced by the Nigerian health care financing sources and their effect on the income distribution. Inequities in health care financing sources are of immense policy concern particularly in developing countries such as Nigeria, where high-level income inequality exists, and the cost of medical care is generally financed out-of-pocket (OOP) due to limited access to health insurance. Design/methodology/approach: The Duclos et al. decomposition model provided the theoretical framework for the study. Data were obtained from two waves of the Nigeria General Household Survey (GHS) panel, 2012–13 and 2015–16. The analysis covered 3, 999 households in 2012–13 and 4, 051 households in 2015–16. Two measures of health care financing: OOP payment and health insurance contribution (HIC) were used. The ability to pay measure was household consumption expenditure. Findings: The major inequity issue induced by the OOP payments was vertical inequity. HICs created the problems of vertical inequity, horizontal inequity and reranking among households. Overall both health care financing options were associated with the worsening of income inequality both at the national and sectorial levels in the country. The operations of the NHIS need to be improved to ensuring improved health care coverage for the poor. Originality/value: This paper fulfills an identified need to determine the income redistributive effects (REs) of the social health insurance (SHI) contribution at the national, urban and rural locations overtime.